Determination of the intramammary dose of benzylpenicillin required to maintain an adequate concentration in the milk to inhibit Gram‐positive bacteria in the clinically normal udder for 24 hr. Issue 5 (11th June 2018) - Abbeloos, Elke; Pyörälä, Satu; Rajala‐Schultz, Päivi; Myllys, Vesa
Abstract: The aim of this study was to determine the intramammary dose of benzylpenicillin required to maintain a concentration in the milk above the MIC for the Gram‐positive bacteria that cause mastitis. The product used in this study was a commercially available procaine benzylpenicillin in an oily suspension with micronized particles. Three dose levels were used: 200, 000, 300, 000, and 600, 000 IU. Concentrations of benzylpenicillin in cow milk and plasma were determined after a single intramammary dose was administered into one quarter of each of the five cows in each treatment group. Samples were analyzed using an HPLC‐MS/MS method, which was validated during the study. Concentrations in the milk were well above the MIC for the target pathogens for all doses tested. There was a linear dose‐dependent increase in the mean AUCs of benzylpenicillin concentrations in plasma and milk. At the first milking, 12 hr after dosing, there was a significant difference between the mean milk benzylpenicillin concentrations in cows treated with a dose of 600, 000 IU, and those treated with 200, 000 or 300, 000 IU. Although this study shows a linear relationship between the dose of procaine benzylpenicillin administered and the concentration in the milk in the healthy udder, it would be useful to conduct studies on cows with mastitis to define the optimum dose and duration of intramammary treatment with benzylpenicillin.